Trust, waqf literacy and cash waqf intention in Islamic boarding schools: A theory of planned behavior - Qomar, Moh. Nurul; Ratnasari, Ririn Tri; Hasyim, Fuad; Putra, Trisno Wardy; Hidayati, (Universitas Negeri Surabaya, 2024)
This research aimed to explore the factors influencing individuals' inclination to contribute funds as waqf to Islamic boarding schools in Indonesia. Additionally, the Theory of Planned Behaviour (TPB) was used as the conceptual framework to analyse human behaviour. In this context, trust and waqf literacy were evaluated and identified as determinants of cash waqf intention. The partial least squares structural equation modelling (PLS-SEM) method was used to completely analyse and assess the model. Meanwhile, the questionnaires were distributed electronically to 436 respondents in Indonesia. The results showed that subjective norms, trust, and waqf literacy had a direct effect on attitudes. However, these variables did not have a direct impact on the intention to donate cash waqf in Islamic boarding schools. Attitudes did not influence the intention to donate cash waqf while perceived behavioural control (PBC) had a substantial impact on the variable.